THE DIGITAL FRONTIER: STRATEGIES AND TOOLS FOR CULTIVATING EDUCATIONAL-STRATEGIC COMPETENCE FOR PRE-SERVICE TEACHERS - Vira Svyrydiuk; Ostap Bodyk; Larysa Kalinina; Nataliya Prokopchuk; Nina Khrystych (Інформаційні технології і засоби навчання)
Digital tools constitute an integral component in the organization of contemporary foreign language environment. The incorporation of Internet technologies into the educational process stimulates the cognitive activity of learners. This article explores potential avenues for cultivating educational-strategic competence in German-language writing through the use of the MOODLE educational platform and Padlet board. The scientific novelty of the research is that overcoming barriers by pre-service teachers in using the educational platform Moodle and the Padlet board ensures the formation of educational-strategic competence in German language writing and intercultural communicative competence. The authors examine the tasks and skills associated with educational-strategic competence, aiming at enhancing the writing skills of pre-service teachers and foster further intercultural foreign language communicative competence.